General aspects of Irazú Volcano National Park - Varela, Alejandra (2011)
The Irazú Volcano National Park was created on July 30th, 1955. Its name probably comes from a native word “Istarú”, which means Thunder and Earthquake Mountain. This National Park has two scenic areas: The Craters area and Prusia area. Visitors can enjoy trails and do recreational activities. Irazú summit (3432 m a.s.l.) offers a variety of attractions: volcanic landsforms (craters, crater lakes, cones), and elsewhere it is possible to find species common of subalpine paramo elevations.